The design of reusable endosurgical grasper using compliant mechanism / Solehuddin Shuib...[et al.] - Shuib*,, Solehuddin; Ahmad Fuzi, Amir Haqim; Sh Ahmad, Siti Mariam (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Endoscopic Surgical Graspers are the basic tools in endoscopic surgery techniques. These graspers act as tissue and organ grasper during the surgery. Endoscopic graspers are designed in various forms for various types of surgery. This project is a research on the tools for endoscopic surgery techniques. This project involves designing, modification of tools, analyzing mechanism and materials used and the cost of making an endoscopic grasper using compliant mechanism concept. Five novel design concepts have been rendered as probable approaches to the tool grip. These models were then evaluated respectively to determine the best design. Commercial CAD and finite element software will be used. CATIA is used for developing the part modelling and detailing, while ANSYS software is used to analyze the feasibility of the designed models. The ANSYS software will be used to design the endoscopic grasper and carry out the analysis of maximum affirmation and displacement on the components of the endoscopic grasper through Finite Element Analysis (FEA). The design prototype will be produced. It is hoped that the design will reduce the cost of surgical operations and the disposal of surgical instrument that will help to improve the environment.